Uma estratégia de aprendizagem cooperativa para desenvolvimento do pensamento computacional por meio de atividades de produção de Jogos Digitais - Angelo Jesus; Ismar Frango Silveira (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2019)
Including Computational Thinking (CT) in the classroom can bring great advances to education. Through Computational Thinking, students can exercise logical reasoning, solve complex problems, deal with abstraction and other skills. Collaboration is also a key aspect of learning. Social interactions between students wreaked from cooperative learning methods could contribute to build knowledge in different ways. This article describes the development of a Cooperative Learning strategy to support and mobilize CT skills in students. Fundamental features of cooperative learning concepts from the literature have been studied and designed to fit the proposed learning strategy. Also, the proposed method uses Game Development approaches in order to engage learners. In addition to being present in students' daily lives, digital games enable direct interaction by giving feedbacks to student commands via animated graphics. A strategy analysis was performed through activities carried out with groups of students from the elementary schools' final series. We investigated the created artifacts and the interactions between students. The results showed that the approach was capable to mobilize CT problem-solving strategies and reflections about social interactions in the group.